Pengaruh Technostress dan Self-Efficacy Terhadap Kepuasan Kerja Freelance Content Creator di Komunitas Smiling West Java Ambassador Kota Bandung - Gumilang Puntang Aulia, Intan; Rahayu, Yulianita; Zuhriatusobah, Juju; Soleh Permana, Arie (Journal of Innovation in Management, Accounting and Business, 2025)
Job Satisfaction is an individual's positive or negative feelings towards his job, which reflects the extent to which expectations match reality in the work environment. This study aims to analyze the effect of Technostress and Self-Efficacy on job satisfaction of Freelance Content Creator in Smiling West Java Ambassador Community in Bandung City. The method used is quantitative with data collection techniques through documentation, interviews, questionnaires, and observation. The population of this study were all community members totaling 78 people, and the sampling technique used the saturated sample method, where the entire population was sampled. The results of the analysis through the Partial Significance Test (t test) show that Technostress has a negative and significant effect on Job Satisfaction, while Self-Efficacy has a positive and significant effect on Job Satisfaction. Simultaneous Significance Test (F Test) shows that Technostress and Self-Efficacy simultaneously have a significant effect on Job Satisfaction.